The Feasibility of Detecting Biosignatures in the TRAPPIST-1 Planetary System with JWST - Victoria S. Meadows; Andrew P. Lincowski; Jacob Lustig-Yaeger (The Planetary Science Journal, 2023)
The James Webb Space Telescope (JWST) provides the first opportunity to detect gases in the atmospheres of M-dwarf terrestrial planets and search for signs of life. Here we determine the detectability of a comprehensive suite of biosignature gases that may have been episodically prevalent across Earth’s history. We used coupled 1D climate–photochemical models to generate synthetic inhabited terrestrial planetary environments for TRAPPIST-1 d and e. These encompass cloudy and/or hazy Archean-Earth-like environments with either a dominant sulfur- or methane-producing biosphere, as well as clear and cloudy modern-Earth-like environments with photosynthetic oxygen-producing biospheres. We generate transmission spectra and assess the likely detectability of different biosignatures with JWST. Our simulations suggest that biogenically generated O _2 and its photosynthetic by-product O _3 will likely be extremely difficult to detect. We explored the detectability of methyl chloride (CH _3 Cl) as an alternative indicator for a photosynthetic biosphere but find that it will likely require significantly higher global surface fluxes than Earth’s. We find that the CH _4 and CO _2 disequilibrium pair is potentially detectable in ∼10 transits for both the methanogen-dominated Archean-like environment and the modern photosynthetic-dominated biosphere—even in cloudy atmospheres. Organic haze and methyl mercaptan are other potential biosignatures for the Archean. Given the likely difficulties in observing an oxygenic-photosynthetic biosphere with JWST, we conclude that the methanogenic biosphere revealed by the combination of outgassed CO _2 in the presence of methanogenically generated CH _4 may be the most persistent detectable biosignature for an Earth-like planet.